Decoupling control of both turbine power and reactor power in a marine use multi-reactor and multi-turbine nuclear power plant. (February 2021) - Nuerlan, Areai; Wan, Jiashuang; Wang, Pengfei; Zhao, Fuyu
Abstract: In multi-reactor and multi-turbine nuclear power plants (MMNPP), several reactor units working in parallel provide steam to turbines that generate power for different purposes. Reactor units can be classified as load following reactors (LFRs) and fixed-power reactors (FPRs) to provide more flexible, adaptable and secure power sources to the loads. Due to a common steam header that all reactors and turbines are connected to, power change in one turbine can interfere with the steady operation of other turbines (and their power output) when operating in load following scenarios. For the same reason, changes in the power output of LFRs can influence that of FPRs. These may threaten the stable and safe operation of the plant, especially in the harsh environments of the sea and ocean. To reduce the coupling effect between each turbine and that between each reactor, this paper propose three kinds of decoupling control methods. One of them is based on feedforward compensation decoupling control method, aimed at decoupling the turbine power outputs only. Another one is composed of a feedforward feedwater controller and a feedback header steam pressure controller, designed to reduce the mutual interference between reactor power outputs. The third control strategy is the combination of above two methods, decoupling turbine power outputs as well as reactor power simultaneously. Simulation results indicate that among the proposed strategies, the second and third method provide better performance than the first one, by reducing both of the coupling effects to the minimum with faster power tracking capability and strong robustness. Graphical abstract: Image 1 Highlights: The coupling effects of reactors and turbines in MMNPPs are analyzed and proved to be strong. Three decoupling controllers are designed to address the coupling effects. The controller based on feedforward compensation method and feedforward-feedback method provides the best performance. Coupling effects in both reactors and turbines are minimized.